Cholesterol degradation in archaeological pottery mediated by fired clay and fatty acid pro-oxidants. Issue 50 (12th December 2018) - Hammann, Simon; Cramp, Lucy J.E.; Whittle, Mathilda; Evershed, Richard P.
Graphical abstract: Highlights: Cholesterol was degraded when dosed on powdered clay and heated at 100 °C. Dehydration products and cholesterol oxidation products could be detected. Fatty acids in tenfold or higher excess promoted drastic cholesterol degradation. This explains the absence of dietary sterols in archaeological lipid residues. Abstract: Cholesterol is generally absent in animal fat residues preserved in archaeological ceramic vessels. It is known from edible oil refining that during bleaching with activated clay sterols are degraded, largely via oxidation. Laboratory heating experiments using fired clay from replica pottery vessels promoted rapid degradation of cholesterol via oxidation. Furthermore, heating cholesterol with fatty acids (saturated and unsaturated) revealed additional degradation to occur independently of the ceramic matrix. As both conditions are met in archaeological pottery during animal (and plant) product processing involving heating, the very rare detection of sterols in organic residues can be explained.